Analysis of archives management in the administration section in elementary schools - Sumarni Sumarni; Aldo Redho Syam; Panessai Sir (AL-ASASIYYA: Journal Of Basic Education, 2020)
This study aims to determine the implementation of archive management in the administration section of public elementary schools in Pammana District, Wajo Regency, South Sulawesi. This study used a qualitative descriptive approach with a single fixed research strategy. The sampling technique used was purposive and snowball sampling. Sources of data used are informants, places and events, as well as archives and documents. Data collection techniques by interview, participant observation and documentation. The data analysis technique used is an interactive analysis model. Based on the results of the research, it can be concluded that the implementation of archive management in the administration section of public elementary schools in Pammana District, Wajo Regency, South Sulawesi is implemented with a fairly good archive management system. This is marked by the management of records that have used the principle of a combination of centralization and decentralization, in the form of active, in-active and static records. The implementation of archive management in the administration section of public elementary schools in Pammana Subdistrict, Wajo Regency, South Sulawesi was also found to be a number of obstacles, namely: the lack of knowledge of employees about archiving; insufficient archive storage place; lack of attention to archival storage. The efforts that have been made by the administration department of public elementary schools in Pammana District, Wajo Regency, South Sulawesi to overcome these obstacles by involving administrative staff in training on archiving; repairing and changing the layout and layout of archives in the archival room of public elementary schools in Pammana District, Wajo Regency, South Sulawesi; and improve and add filing facilities according to the needs required by administrative staff.